Peptidorhamnomannans From Scedosporium and Lomentospora Species Display Microbicidal Activity Against Bacteria Commonly Present in Cystic Fibrosis Patients - de Oliveira, Evely Bertulino; Xisto, Mariana Ingrid Dutra da Silva; Rollin-Pinheiro, Rodrigo; Rochetti, Victor Pereira; Barreto-Bergter, Eliana (Frontiers in Cellular and Infection Microbiology, 2020)
Scedosporium and Lomentospora species are filamentous fungi that cause a wide range of infections in humans. They are usually found in the lungs of cystic fibrosis (CF) patients and are the second most frequent fungal genus after Aspergillus species. Several studies have been recently performed in order to understand how fungi and bacteria interact in CF lungs, since both can be isolated simultaneously from patients. In this context, many bacterial molecules were shown to inhibit fungal growth, but little is known about how fungi could interfere in bacterial development in CF lungs. Scedosporium and Lomentospora species present peptidorhamnomannans (PRMs) in their cell wall that play crucial roles in fungal adhesion and interaction with host epithelial cells and the immune system. The present study aimed to analyze whether PRMs extracted from Lomentospora prolificans, Scedosporium apiospermum, Scedosporium boydii, and Scedosporium aurantiacum block bacterial growth and biofilm formation in vitro. PRM from L. prolificans and S. boydii displayed the best bactericidal effect against methicillin resistant Staphylococcus aureus (MRSA), Burkholderia cepacia, and Escherichia coli, but not Pseudomonas aeruginosa, all of which are the most frequently found bacteria in CF lungs. In addition, biofilm formation was inhibited in all bacteria tested using PRMs at minimal inhibitory concentration (MIC). These results suggest that PRMs from the Scedosporium and Lomentospora surface seem to play an important role in Scedosporium colonization in CF patients, helping to clarify how these pathogens interact to each other in CF lungs.